2013
DOI: 10.1108/09513541311329878
|View full text |Cite
|
Sign up to set email alerts
|

Identifying highly effective urban schools: comparing two measures of school success

Abstract: PurposeThe purpose of this paper is to provide an empirical comparison of two measures of school success – a value‐added assessment system and the federally‐mandated system of adequate yearly progress (AYP) – to identify highly effective urban schools in the USA and to explore the predictive relationship between evidence‐based decision‐making and school improvement.Design/methodology/approachA total of 204 urban schools with 6,684 teachers and 149,665 students in grades 1 through 10 participated in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…This has resulted in intensively research on the effectiveness of schools (Day, Gu and Sammons, 2016). While some of the studies on school effectiveness focus on the effectiveness levels of schools or on determining the characteristics of effective schools (Hofman and Hofman, 2011;Wang et al, 2013), some studies have focused on factors affecting school effectiveness (Bolanle, 2013;Tatlah and Iqbal, 2012). The results of the various studies have shown that school principals' leadership behaviors are an important factor affecting school effectiveness (Tatlah and Iqbal, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has resulted in intensively research on the effectiveness of schools (Day, Gu and Sammons, 2016). While some of the studies on school effectiveness focus on the effectiveness levels of schools or on determining the characteristics of effective schools (Hofman and Hofman, 2011;Wang et al, 2013), some studies have focused on factors affecting school effectiveness (Bolanle, 2013;Tatlah and Iqbal, 2012). The results of the various studies have shown that school principals' leadership behaviors are an important factor affecting school effectiveness (Tatlah and Iqbal, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Trujillo, 2013). Okul etkililiği üzerine yapılan birçok çalışmada etkili okulun; 1) güçlü öğrenme çevresi, 2) güçlü öğretimsel liderlik, 3) yüksek personel morali, 4) delile dayalı karar verme, 5) yüksek öğretmen yeterliği şeklinde beş özelliğinin olduğu ortaya çıkmıştır (Hofman ve Hofman, 2011;Sammons, Gu, Day ve Ko, 2011;Wang, Walters ve Thum, 2013). Bununla birlikte etkili bir okul, öğretmenleri çalışmaya teşvik edici bir vizyona, açık ortak amaç ve hedeflere, etkili bir iletişime, çocukların görüşlerini ifade edebilme ve öğretmenlerle etkileşimi kurabilmeyi destekleyen, çocukların kişisel ve sosyal gelişimini besleyen, nitelikli personel ve iyi uzmanlara sahip olan iyi bir çevredir (Purkey ve Smith, 1993).…”
Section: Introductionunclassified
“…The concept is part of a more comprehensive theory of school effectiveness, claiming that certain schools are more successful than others in creating the shared meaning and common goals needed in order to introduce adolescents into adulthood and to counteract negative effects of external factors. Important features of effective schools are a pedagogy that focuses on clear goals, constructive feedback to the students, providing a safe and orderly environment, a strong academic focus, and positive home-school relations [ 27 , 28 , 29 , 30 ]. Empirical studies have shown that schools with such features are characterized by higher school performance [ 24 , 25 ], lower levels of delinquency [ 31 ] and less alcohol and drug use among their students [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Este considera un amplio conjunto de indicadores de resultados de los establecimientos del país, y ha sido utilizado con éxito en otros estudios focalizados en la educación primaria chilena (Bellei, Valenzuela, Vanni y Contreras, 2014). La selección de escuelas efectivas da cuenta del objetivo general del estudio más amplio y recoge la evidencia empírica que muestra, entre otros aspectos, que estas se caracterizan por un liderazgo pedagógico fuerte, docentes con altos niveles de auto eficacia y comprometidos con la mejora escolar (Wang, Walters y Thum, 2013).…”
Section: Muestraunclassified